A case of permanent pacemaker implantation from the left side in persistent left superior vena cava – Technical challenges in a rare presentation - Sharma, Awadhesh Kumar; Prakash, Neeraj; Sarraf, Sameer (Indian Journal of Case Reports, 2020)
Abnormalities of the systemic venous system are not uncommon. Two well-known systemic venous anomalies are the persistent left superior vena cava (PLSVC) and interrupted inferior vena cava. PLSVC is usually detected and comes as a surprise for the cardiologist during cardiac permanent pacemaker implantation. We report the case of a 65-year-old male who had a history of recurrent syncope and diagnosed with a complete heart block 8 months back. For which, a single-chamber VVIR pacemaker was implanted through the right subclavian vein at Delhi. The patient was a known case of diabetes mellitus and had poorly controlled blood sugar levels. At present, the patient presented to our center with pacemaker pocket site infection and it was first decided to explain the right-sided permanent pacemaker, insert temporary pacemaker, and implant the new pacemaker on the left side through the left subclavian vein. In this case, during procedure, PLSVC detected accidentally; so, we discuss the challenges we faced during the right ventricular lead placement through PLSVC.